Rosyjskie czynniki rządowe wobec reformy szkolnej Aleksandra Wielopolskiego w świetle petersburskiego rękopisu ekspertyzy prawnej zatytułowanej Uwagi nad projektem stworzenia instytucji naukowych w Królestwie Polskim opublikowanym w polskiej gazecie »Dziennik Powszechny« - Szpoper, Dariusz (Czasopismo Prawno-Historyczne, 2018)
A bill concerning public education together with an accompanying explanatory statement were created between June and October 1861. The aforementioned bill and justification were created under the direction of count Alexander Wielopolski, marquis Gonzaga-Myszkowski, the Presiding Chief Director in the Governmental Committee of Faith and Public Enlightenment of the Kingdom of Poland. Both of these documents were published on the pages of a newspaper entitled “Public Daily” (Polish Dziennik Powszechny) in Warsaw. The Russian authorities in Saint Petersburg ordered a legal opinion to be drawn up in November-December of 1861. Its contents were used to analyze the proposed education reform in the Kingdom of Poland.